이질아메바에 의한 인체 대장상피세포주 HT-29에서의 interleukin-8 유전자의 발현 - 김정목(Jung Mogg Kim); 정현채(Hyun Chae Jung); 임경일(Kyung-Il Im); 조양자(Yang-Ja Cho); 김정룡(Chung Yong Kim) (Korean journal of parasitology, 1995)
The protozoan parasite, Entcmoeba histoIWticc, is one of major causative agents of intestinal disease all over the world. In acute experimental infection, the early host response to 5. histoIHtica is characterized by an infiltration of neutrophils. However, the chemotactic signal for this response is not well known. Based on the (jading that human epithelial cells produce the potent neutrophil chemoattractant and activator, interleukin-8 (IL-8), IL-8 gene expression was examined thoroughly in human colon epithelial cells exposed to 5. histolvtica trophozoites. Cellular RNAs were extracted from HT-29 or Caco-2 human colon epithelial cells exposed to 5. histoLvtica trophozoites for 30 minutes, 1 and 3 hours. IL-8 mRNA transcripts were measured by reverse transcriptional polprnerase chain reaction (RT-PCR) using synthetic standard RNA. The number of IL-8 mRNA molecules increased from 30 minutes to 3 hours of exposure period, reaching 3.1 H 107 molecules/ug of total RNA. Expression pattern of IL-8 mRNA transcripts was parallel to the amounts of IL-8 protein measured by enzyme-linked immunosorbent assay (ELISA) . Lysates of 5. histoIVtica also induced expression of mRNA for IL-8 in colon epithelial cells. These results sugf:esc that acute inflammatory reaction by 5. histoIVticc may be initially triggered by proinflammatory cytokines such as IL-8 secreted from epithelial cells of the colon. 이질아메바에 의한 장염 환자의 조직 또는 이질아메바를 실험적으로 감염시킨 동물의 조직 검사에서 호중구의 침윤이 특징적으로 관찰된다. 그러나 이와같은 호중구의 침윤을 설명할 수 있는 기전에 대한 연구는 매우 미흡하다. 따라서 본 연구자들은 아메바 감염 초기에 인체 대장상피 세포에서 interleukin-8(IL-8)이 유도되어 호중구 침윤과 같은 염증반응이 유발될 것이라는 가설을 설정하였다. 이를 위하여 인체 대장상피세포주인 HT-29에 이질아메바 영양형을 실험적으로 노출시킨 뒤 발현되는 IL-S mRNA를 역전사 중합효소법(reverse transcriptional polymerase chain reaction, RT-PCR)으로 검사함과 퐁시에 발현된 IL-8 mRNA를 인공적으로 합성시킨 표준 RNA와 RT-PCR법을 이용하여 정량하였다. 실험 결과 이질아메바 영양형에 노출된 30분 후 부터 IL-8 mRAN가 발현되기 시작하였다 그리고 그 발현 분자수는 노출 시간의 증가에 따라 계속 증가하여 3시간 대에는 $3.1{\;}{\times}{\;}10^7{\;}molecules/\mu\textrm{g}$ total RNA를 나타내었다. 동시에 IL-8 mRNA의 발현은 노출시킨 이질아메바 영양형의 수에 비례하였다. 즉 HT-29/아메바 영양형의 비율이 10:1인 경우 IL-8 mRNA의 발현 분자수는 $1.2{\;}{\times}{\;}10^7{\;}molecules/\mu\textrm{g}$ total RNA로 나타났다. 이와같은 IL-8 mRNA의 발현은 IL-8 단백질 분비로 이어짐을 ELISA 검사로 확인할 수 있었다. 한편 이질아메바 파쇄액(Iysate)도 대장상피세포군인 Caco-2에서 IL-8 mRNA발현을 유도하였다. 결론적으로 본 실험은 이질아메바 감염 초기에 대장상피세포로 부터 IL-8이 발현되며, 이에 의하여 염증반응이 촉발될 가능성이 있음을 시사해 준다.